2020
DOI: 10.2147/dddt.s248104
|View full text |Cite
|
Sign up to set email alerts
|

<p>Glycine Improves Ischemic Stroke Through miR-19a-3p/AMPK/GSK-3β/HO-1 Pathway</p>

Abstract: Purpose: To explore the molecular mechanism of glycine in improving ischemic stroke. Patients and Methods: The serum samples of patients with ischemic stroke and healthy people were compared. The ischemic stroke model of PC12 cells was established by oxygenglucose deprivation (OGD). qPCR quantified miR-19a-3p and AMPK mRNA, and protein expression was detected by Western blot. MTT was used to detect cell activity. Flow cytometry was used to detect cells. Glucose metabolism kit was used to detect glucose intake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…MiR-19a-3p can suppress LPS/IFN-g-induced M1 macrophage polarization via inhibiting STAT1 (signal transducer and activator of transcription-1) (60). In addition, glycine regulates miR-19a-3p/AMPK pathway to alleviate ischemic stroke injury (61). Therefore, glycine may promote M1 macrophage polarization by regulating miR-19a-3p (Figure 2C).…”
Section: Glycine Alters Micrornas In Macrophagesmentioning
confidence: 99%
“…MiR-19a-3p can suppress LPS/IFN-g-induced M1 macrophage polarization via inhibiting STAT1 (signal transducer and activator of transcription-1) (60). In addition, glycine regulates miR-19a-3p/AMPK pathway to alleviate ischemic stroke injury (61). Therefore, glycine may promote M1 macrophage polarization by regulating miR-19a-3p (Figure 2C).…”
Section: Glycine Alters Micrornas In Macrophagesmentioning
confidence: 99%
“… 12 More importantly, in transient ischemic attack (TIA), a complication of CAS, glycine improves TIA by regulating miR-19a-3p to inhibit glucose metabolism, inflammation, and apoptosis. 13 …”
Section: Introductionmentioning
confidence: 99%
“…12 More importantly, in transient ischemic attack (TIA), a complication of CAS, glycine improves TIA by regulating miR-19a-3p to inhibit glucose metabolism, inflammation, and apoptosis. 13 Although the function of miR-19a-3p in CAS-related diseases has been described in detail, the clinical potential of miR-19a-3p in asymptomatic CAS remains unknown. Therefore, according to the current research status of CAS, we examined the serum miR-19a-3p levels of recruited asymptomatic CAS patients and healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven in many studies that inhibition of GSK-3β effectively upregulates HO-1 protein expression (Jiang et al, 2015;Yan et al, 2020). As a result, enhancement of HO-1 via GSK-3β inactivation (GSK-3β/ HO-1 pathway) plays a crucial role in improving ischemic stroke (Chen et al, 2020). In summary, HO-1 up-regulation is an adaptive response to oxidative stress in the body.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, upregulation of heme oxygenase-1 (HO-1) via GSK-3β deactivation through Ser9 phosphorylation could remarkably suppress the oxidative stress damage (Duan et al, 2019). It has been reported that glycine improved ischemic stroke via activation of the GSK-3β/HO-1 pathway (Chen et al, 2020). These studies suggested that the diminution of oxidant stress by activation of GSK-3β/HO-1 pathway is an effective therapeutic strategy for ischemic stroke prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%